UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS MELALUI WASKAT KEPALA SEKOLAH PADA SMP NEGERI 4 RIMBA MELINTANG KABUPATEN ROKAN HILIR: (Efforts To Increase Teachers’ Discipline In The Classroom through the Principal Waskat at SMP Negeri 4 Rimba Melintang Rokan Hilir - Sariana Sariana (UIR Press, 2017)
The purpose of this study was to determine the increase discipline in the presence of teachers teaching in the classroom through waskat Principal at SMP Negeri 4 Rimba Melintang Rokan Hilir. This study uses action research design school (PTS) designed two cycles of the first cycle and the second cycle. The subjects were teachers of SMP Negeri 4 Transverse Rimba Rokan Hilir. Analysis of data using qualitative data analysis derived from primary data and empirical. Based on the findings, it was concluded that waskat Principal, Discipline Teachers can increase in the presence of teaching in the classroom, it is seen 84% of respondents stated that waskat Principal very role in improving teacher discipline, especially in the presence of classroom teaching..